Start Up Talk to Entrepreneur: Merubah Mindset Shift dari Follower Menjadi Owner - Hadi Ismanto; Vembri Aulia Rahmi; Muhammad Rosyihuddin (Lembaga Pengembangan Kinerja Dosen, 2026)
This Community Service (PkM) activity was implemented in the form of an entrepreneurship seminar. This seminar strategically raised the theme